2018
DOI: 10.1021/acsami.8b05607
|View full text |Cite
|
Sign up to set email alerts
|

pH-Sensitive Multiligand Gold Nanoplatform Targeting Carbonic Anhydrase IX Enhances the Delivery of Doxorubicin to Hypoxic Tumor Spheroids and Overcomes the Hypoxia-Induced Chemoresistance

Abstract: Hypoxia is a common feature of solid tumors contributing to resistance to chemotherapy. Selective delivery of chemotherapeutic drugs to hypoxic tumor niche remains an unsolved issue. For this purpose, we constructed a gold nanoplatform targeting carbonic anhydrase IX (CA IX) epitope, which is overexpressed in hypoxic tumor cells versus in normal tissues. We designed compatible low-molecular weight carbonic anhydrase inhibitor (CAI) ligands and doxorubicin (Dox) ligands and optimized protocols for efficient dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 72 publications
2
37
0
Order By: Relevance
“…Anti-epileptic drugs topiramate 8 and zonisamide 9 are also potent CA inhibitors (CAIs). Other promising CA inhibitors are currently under advanced clinical stages in the treatment of hypoxic tumors [1,6,[9][10][11][12][13] and were also used recently in the selective delivery of toxic drugs to tumors [14,15]. Slower isozymes can be activated with CA activators, with potential applications in memory and learning enhancement [1,[16][17][18][19][20][21][22][23] The boundary between CA activation and inhibition was also revealed recently [24].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-epileptic drugs topiramate 8 and zonisamide 9 are also potent CA inhibitors (CAIs). Other promising CA inhibitors are currently under advanced clinical stages in the treatment of hypoxic tumors [1,6,[9][10][11][12][13] and were also used recently in the selective delivery of toxic drugs to tumors [14,15]. Slower isozymes can be activated with CA activators, with potential applications in memory and learning enhancement [1,[16][17][18][19][20][21][22][23] The boundary between CA activation and inhibition was also revealed recently [24].…”
Section: Introductionmentioning
confidence: 99%
“…Except one study using silica nanoparticles coated with the anti-CA IX MAb M75 [62], all other studies exploited carbonic anhydrase inhibitors. As CA inhibitors are principally acting towards diverse CA isoforms due to similarities in their active sites, selectivity to CA IX was conferred by diverse carriers [45], gold nanoparticles [46], pH-responsive nanoparticles [47], polymer-based photodynamic nanoinhibitor particles [48]. However, the approaches using inhibitors principally differ from the approach using monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated the modification of screen-printed carbon electrodes by assembling graphene oxide to obtain electrochemical immunosensors with immobilized antibodies specific to mucin 1, which is a well-known tumor marker for a variety of malignant tumors [44]. Efforts to detect or target CA IX have been mostly focused on development of diverse nanoparticles decorated by inhibitors of Carbonic anhydrases with modifications conferring selectivity towards CA IX and/or other cell surface isoforms [45,46,47,48]. These approaches require access to active site of the enzyme, whereas the antibodies can bind CA IX even in an inactive state.…”
Section: Introductionmentioning
confidence: 99%
“…This concept allows for the destruction of cells in hypoxic tumors and can be applied in combination with photothermal therapy. Shabana et al took advantage of carbonic anhydrase IX (CA IX) overexpression that occurs in hypoxic TME to develop AuNPs functionalized with DOX and a CA inhibitor ligand, that allows active targeting to hypoxic tumors (Shabana et al, 2018). DOX is grafted to the NPs through a hydrazone group that is cleaved in acidic pH, releasing the drug.…”
Section: Targeting Tme Via Gold Nanoparticlesmentioning
confidence: 99%